Androcentric Hegemony in the Old Testament: Hermeneutical Stance, Challenges and Transitions - Antwi, Emmanuel Kojo Ennin ca. 20./21.Jh. (Ghana journal of religion and theology, 2025)
The role and functions of women in some societies are presented in such a way that women seem to be inferior to men. Judeo-Christian scriptures have been blamed for contributing to such a disparity between men and women. This paper analyses the androcentric hegemony in the Old Testament and its impact on contemporary Judeo-Christian thought. It examines some Old Testament texts, highlighting the functions of women, and their theological development in the New Testament. Women performed significant functions in the Judeo-Christian scriptures; however, their role has been overshadowed by male dominance. This is due to the androcentric hegemony in the then biblical world. Feminist movements and female theologians have sought to redefine the narrative in their search to raise the image of “woman.” Present-day Christian churches have come to grips with the situation and have begun to assign more roles and functions to women in contemporary Judeo-Christian practice.